First record of Discleroderma Kieffer (Hymenoptera, Bethylidae) from China and Republic of the Congo, with description of two new species - Wang, Chun-Hong; Chen, Xue-Xin (Zootaxa, 2024)
The genus Discleroderma Kieffer is recorded from China and Republic of the Congo for the first time. Two new species are described and illustrated: D. congoense sp. nov., D. xizangense sp. nov. from Republic of the Congo and China, respectively. An updated key to the world species of this genus is provided.